(untitled) (Journal of Civil Engineering Researchers, 2022)
Pervious concrete contains a mixture of water, cement, coarse aggregates and little or no fine aggregates. Pervious concrete is increasingly known as an environmentally friendly material due to its usefulness in improving water quality by removing all suspended solid particles in the flood, reducing the flow of flood water, reducing the heat island effect and other environmental benefits. In this article, the results of valid research on the physical (slump, density, porosity, water permeability) and mechanical (compressive strength, flexural strength, splitting tensile strength) properties of Pervious concrete have been briefed and reported.